2010
DOI: 10.1007/s11738-010-0552-4
|View full text |Cite
|
Sign up to set email alerts
|

Leaf–water relations and ion concentrations of the halophyte Atriplex hortensis in response to salinity and water stress

Abstract: The impact of salinity and water stress was analyzed in the xero-halophyte Atriplex hortensis using two varieties: green orach (A. hortensis var. purpurea) and red orach (A. hortensis var. rubra). A. hortensis L. is a C 3 species well adapted to salt and drought conditions. To collect information on the physiological impact of different salt and water deficit levels on their water stress resistance, plants were exposed for 3 months to solution containing four levels of NaCl or to water stress regimes including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…These trends were not so clearly seen in perennial species, where several succulent and semi-succulent plants showed high Ca concentrations (potentially the same species that showed a tendency to accumulate S and could be growing on gypsum-rich soils). Our findings for annual plants are in agreement with several previous reports on the incompatibility of Ca and Na in plant cells under salt stress (Grattan and Grieve, 1992;Kachout et al, 2011;Krüger and Peinemann, 1996;Naidoo, 1994;Tipirdamaz et al, 2006). Furthermore it may be explained by the lower selectivity of Ca under high Na by transport systems and the ability of pseudo-halophytes and facultative-halophytes to favor Ca and avoid Na uptake when growing in saline environments (Albert and Popp, 1977;Grattan and Grieve, 1992;Kudo et al, 2010).…”
Section: Most Annual Succulent Eu-halophytes Show Low Ca Concentrationssupporting
confidence: 93%
See 2 more Smart Citations
“…These trends were not so clearly seen in perennial species, where several succulent and semi-succulent plants showed high Ca concentrations (potentially the same species that showed a tendency to accumulate S and could be growing on gypsum-rich soils). Our findings for annual plants are in agreement with several previous reports on the incompatibility of Ca and Na in plant cells under salt stress (Grattan and Grieve, 1992;Kachout et al, 2011;Krüger and Peinemann, 1996;Naidoo, 1994;Tipirdamaz et al, 2006). Furthermore it may be explained by the lower selectivity of Ca under high Na by transport systems and the ability of pseudo-halophytes and facultative-halophytes to favor Ca and avoid Na uptake when growing in saline environments (Albert and Popp, 1977;Grattan and Grieve, 1992;Kudo et al, 2010).…”
Section: Most Annual Succulent Eu-halophytes Show Low Ca Concentrationssupporting
confidence: 93%
“…2, Table 4). Previous studies have shown similarly high Na and reduced K concentrations in halophytes (Grattan and Grieve, 1992;Gulzar et al, 2003;Kachout et al, 2011;Noaman, 2004;Parida and Das, 2005;Taleahmad et al, 2013). Potassium is an essential macronutrient in plant cells, with a key role in many important physiological processes, such as the regulation of stomatal functions, or the adjustment of cell water potential (Noaman, 2004;White and Karley, 2010).…”
Section: Sodium Could Replace Potassium In Metabolic Processes Of Eu-mentioning
confidence: 74%
See 1 more Smart Citation
“…However, K + , Ca 2+ and Mg 2+ decreased in response to water and salt stress. Cl -concentration increased in response to salt stress in all tissues, but water stress had no impact on this parameter (Kachout et al, 2011). Regarding osmoregulation in the coconut palm, proline's contribution to the overall osmotic adjustment in ecotypes of BGD was recently shown to be low (Gomes et al, 2006;Gomes & Prado, 2007) because: (1) proline concentration was reduced to control levels upon rewatering, whereas osmotic potential did not increase and even decreased in re-watered plants; and (2) the patterns of the two coconut ecotypes evaluated for proline accumulation did not reflect their relative behaviors in terms of osmotic adjustment.…”
Section: Osmoregulation (The Participation Of Organic and Inorganic Smentioning
confidence: 88%
“…Data include species, taxonomic family, habitat (freshwater, coastal or marine), growth form (forb-herb, graminoid or shrub), environmental conditions at the time of collection (including salinity for marine plants; in practical salinity units [psu]) and the reference or source of the data.SpeciesFamilyHabitatGrowth/habitEnviron. conditions/salinitySource Acorus americanus AcoraceaeFreshwaterForb-herbBioretention basin (flooded)This study Acorus americanus AcoraceaeFreshwaterForb-herbGreenhouse (flooded)Romanello et al (2008) Arundinaria gigantean PoaceaeCoastalGraminoidDamp soils 100 m from seawaterThis study Atriplex hortensis ChenopodiaceaeFreshwaterForb-herbGreenhouseKachout et al (2011) Bidens sp.AsteraceaeFreshwaterForb-herbGreenhouse (saturated soils)This study Borrichia frutescens AsteraceaeMarineShrubUpper salt marsh/32 psuThis study Carex alata CyperaceaeFreshwaterGraminoidGreenhouse (flooded)Touchette et al (2007) Carex alata CyperaceaeFreshwaterGraminoidGreenhouse (saturated soils)This study Cephalanthus occidentalis RubiaceaeFreshwaterShrubLacustrine wet shorelineThis study Eleocharis sp.CyperaceaeFreshwater…”
Section: Methodsmentioning
confidence: 99%